Body Composition in Preschool Children and the Association With Prepregnancy Weight and Gestational Weight Gain: An Ambispective Cohort Study - Chen, Fangfang; Wang, Jing; Liao, Zijun; Zong, Xinnan; Zhang, Ting; Xie, Xianghui; Liu, Gongshu (Frontiers in Nutrition, 2022)
Objective: To describe the body composition in preschool children and to evaluate the association with prepregnancy BMI and gestational weight gain (GWG). Methods: Children were recruited in their first year in kindergarten (3 years old) and followed up for the next two years. Information during pregnancy and birth was retrieved from medical records. Height, weight, fat mass, fat-free mass and percentage of body fat (FM%) were measured through a bioelectrical impedance analysis for each child visit, and BMI, fat mass index (FMI), and fat-free mass index (FFMI) were calculated. Generalized linear mixed models (GLMMs) were used to evaluate the associations between prepregnancy weight, GWG and the adiposity indicators. Results: A total of 3329 single-birth 3-year-old children were recruited as the baseline population and were followed at 4 and 5 years old. During the three years of follow-up, the mean (±SD) values of BMI, FMI, FFMI and FM% of the children were 15.6 (±1.6) kg/m2, 2.8(±1.3) kg/m2, 12.8(±0.7) kg/m2 and 17.2%(±5.8%), respectively. The prevalence rates of overweight and obesity of mothers before pregnancy were 16.6% and 3.2%, respectively. Mothers were divided into three groups based on GWG: appropriate (1233, 37.0%), excessive (767, 23.0%) and insufficient (1329, 39.9%). GLMMs analyses showed that the preschool children’s BMI, FMI, FFMI and FM% were all significantly positively related to maternal prepregnancy BMI and GWG (all P values < 0.001); the children of mothers who were overweight/obese before pregnancy were more likely to be overweight/obese, high FMI, high FFMI and high FM% at preschool age (all P values < 0.001); although maternal excessive GWG was not correlated with offspring’s overweight/obese (P=0.156), the children of mothers with excessive GWG are more likely to have higher FMI, but not to be with a higher FFMI level than the children of mothers with appropriate GWG. Conclusion: FMI increased with age, while FFMI decreased with age among 3- to 5-year-old children. It is necessary to optimize maternal weight prior to conception and GWG management to improve the health outcomes of the offspring.